Neural Tube Biology With Emphasis on Early Neurulation; A Narrative Review - Hossein Bahadoran; Reza Dadfar; Mohammad Hosein Asadi; Amir Abdolmaleki; Sajad Moghadami (Negah Institute for Scientific Communication, 2022)
Neurulation, as the formation of the basis of the nervous system, is the earliest and crucial stage of embryonic development, affecting the development of other parts of the embryonic body. During neurulation, the neural plate is formed through morphological changes. At the end of this stage, the neural tube is established and the central nervous system could be formed in the future. Although this embryonic process occurs morphologically, the precise study of nervous system evolution can be considered by different gene mutations in rodent embryos. Genetic assessments of embryos can finally cause the accurate discovery of the role of genes in embryo development, the stages of nervous system development, and possible associated diseases. Explanation of new findings in the field of neurulation with emphasis on genetics can be helpful in future embryonic studies, abnormalities, and treatments. Thus, the study of neural plate formation can play an important role in increasing the insight of embryological researchers in this field. In this review article, we aimed to collect basic embryonic data in rodent neurulation to provide important information for more laboratory investigations in this field.